Communicative Interaction оf Participants in the Process оf Promotion оn the Individual Residential Market in Russia - I. V. Hristoforova; I. A. Schmidt (Мир новой экономики)
In order to achieve the maximum possible efficiency of modern management in Russia in the market of individual housing communication should be built considering the relationship between market actors, on the basis of which is formed by the housing promotion object that allows you to improve the economic efficiency of an entity in the long term through the generated values relationships. The article is devoted to the consideration of the interaction of key actors in the private housing market, participating in the promotion: building organisations, Realtor firms and consumers. The subject of research: the process of interaction between construction companies, real estate agents and consumer firms, which formed values which affect the effectiveness of the promotion. Tendencies of the development of the individual residential market on the example of the city of Novosibirsk, which allowed updating communication processes of market agents. Despite massive amounts of residential construction, the sales volume of objects of individual pages.